Insulin-like peptide 3 (INSL3) in congenital hypogonadotrophic hypogonadism (CHH) in boys with delayed puberty and adult men - Abbara, Ali; Koysombat, Kanyada; Phylactou, Maria; Eng, Pei Chia; Clarke, Sophie; Comninos, Alexander N.; Yang, Lisa; Izzi-Engbeaya, Chioma; Hanassab, Simon; Smith, Neil; Jayasena, Channa N.; Xu, Cheng; et al. (Frontiers in Endocrinology, 2022)
Background Delayed puberty in males is almost invariably associated with constitutional delay of growth and puberty (CDGP) or congenital hypogonadotrophic hypogonadism (CHH). Establishing the cause at presentation is challenging, with “red flag” features of CHH commonly overlooked. Thus, several markers have been evaluated in both the basal state or after stimulation e.g. with gonadotrophin releasing hormone agonist (GnRHa). Insulin-like peptide 3 (INSL3) is a constitutive secretory product of Leydig cells and thus a possible candidate marker, but there have been limited data examining its role in distinguishing CDGP from CHH. In this manuscript, we assess INSL3 and inhibin B (INB) in two cohorts: 1. Adolescent boys with delayed puberty due to CDGP or CHH and 2. Adult men, both eugonadal and having CHH. Materials and Methods Retrospective cohort studies of 60 boys with CDGP or CHH, as well as 44 adult men who were either eugonadal or had CHH, in whom INSL3, INB, testosterone and gonadotrophins were measured. Cohort 1: Boys with delayed puberty aged 13-17 years (51 with CDGP and 9 with CHH) who had GnRHa stimulation (subcutaneous triptorelin 100mcg), previously reported with respect to INB. Cohort 2: Adult cohort of 44 men (22 eugonadal men and 22 men with CHH), previously reported with respect to gonadotrophin responses to kisspeptin-54. Results Median INSL3 was higher in boys with CDGP than CHH (0.35 vs 0.15 ng/ml; p=0.0002). Similarly, in adult men, median INSL3 was higher in eugonadal men than CHH (1.08 vs 0.05 ng/ml; p<0.0001). However, INSL3 more accurately differentiated CHH in adult men than in boys with delayed puberty (auROC with 95% CI in adult men: 100%, 100-100%; boys with delayed puberty: 86.7%, 77.7-95.7%). Median INB was higher in boys with CDGP than CHH (182 vs 59 pg/ml; p<0.0001). Likewise, in adult men, median INB was higher in eugonadal men than CHH (170 vs 36.5 pg/ml; p<0.0001). INB performed better than INSL3 in differentiating CHH in boys with delayed puberty (auROC 98.5%, 95.9-100%), than in adult men (auROC 93.9%, 87.2-100%). Conclusion INSL3 better identifies CHH in adult men, whereas INB better identifies CHH in boys with delayed puberty.